Exploring multifaceted impacts of El Niño driven drought on child-headed rural learners' well-being in drought-prone Chivi, Zimbabwe - Munyaradzi Chidarikire; Munyaradzi Saruchera (Interdisciplinary Journal of Rural and Community Studies)
The El Niño phenomenon has led to an increased frequency and intensity of droughts, posing significant challenges for rural communities in sub-Saharan Africa. This qualitative case study examines the multifaceted impacts of El Niño-driven drought on the wellbeing of child-headed households and their educational outcomes in the drought-prone Chivi district of Zimbabwe. The current study aimed to understand how El Niño-induced drought affects the physical, emotional, and socioeconomic wellbeing of child-headed rural learners and how these impacts influence their educational experiences and outcomes. The central research question is: How do El Niño-driven droughts affect the wellbeing and educational trajectories of child-headed households in the Chivi district of Zimbabwe? This study adopted a qualitative research paradigm and a case study design. Fifteen participants were selected using purposive sampling, including young learners from child-headed households and adult community members. Data were collected through two focus group discussions, one with the young learners and another with the adult participants. The data were analysed using thematic analysis. The study found that El Niño-driven droughts exacerbate the vulnerabilities of child-headed households, leading to food insecurity, water scarcity, increased household responsibilities, and mental health challenges. These factors significantly undermine the learners' ability to engage in and succeed in their educational pursuits. The study recommends the implementation of targeted interventions, such as school-based feeding programmes and psychosocial support, to mitigate the adverse impacts of drought on child-headed rural learners.